Analyzing Price, Service Quality, and Innovation as Drivers of Patient Satisfaction Through Repurchase Decisions in Hospitals - Setiawan, Epan; Darma, Gede Sri (International Journal of Economics Development Research (IJEDR), 2025)
Several hospitals do various ways to increase public trust in the services provided, one of which is Siloam Hospital Denpasar. This study aims to provide comprehensive insight into the factors that influence patient satisfaction in conducting Medical Check Ups with a focus on aspects of patient experience, price, service quality, location, innovation, and brand image, and how repurchase decisions can mediate these influences. The research design used in this study is a quantitative approach. The results of the study indicate that price, innovation, and brand image have a positive and significant effect on patient satisfaction with medical check ups at Siloam Hospital Denpasar, while patient experience, service quality, and location have a negative effect on patient satisfaction with medical check ups at Siloam Hospital Denpasar. Price, innovation, and brand image have a positive and significant effect on repurchase decisions for medical check ups at Siloam Hospital Denpasar, while patient experience, service quality, and location have a negative effect on repurchase decisions for medical check ups at Siloam Hospital Denpasar. Repurchase decisions are able to mediate the influence of price, innovation, and brand image on patient satisfaction with medical check-ups at Siloam Hospital, Denpasar, but repurchase decisions are not able to mediate patient experience, service quality, and location on patient satisfaction with medical check-ups at Siloam Hospital, Denpasar.